A Comparison of Dry Eye Diagnostic Tests Between Symptomatic and Asymptomatic Age-Matched Females. (September 2018) - Ngo, William; Srinivasan, Sruthi; Jones, Lyndon
Abstract : Purpose: To quantify the strength of association of dry eye (DE) symptoms to DE diagnostic tests in age-matched females. Methods: Twenty females with DE symptoms (Ocular Surface Disease Index, OSDI, ≥13) were age-matched with 20 females without DE symptoms (OSDI<13) in this cross-sectional study. Noninvasive tear breakup time (NIBUT), ocular staining, meibum quality, number of obstructed meibomian glands (MGs), lid wiper epitheliopathy, Marx line placement, eyelid margin score, Schirmer test, meibography, and visual acuity were assessed in both groups. Results: Twenty participant pairs completed the study. The age (median/interquartile range [IQR]) of the symptomatic group was 60/15 and the asymptomatic group was 62/15. The tests (median/IQR, P value) that were significantly different between the symptomatic group and the asymptomatic group were OSDI (35.4/35.4 vs. 3.1/6.7, P <0.01), NIBUT (2.1/0.7 sec vs. 3.0/3.0 sec, P =0.01), meibum quality (3.0/0.0 grade units vs. 2.0/1.0 grade units, P <0.01), number of obstructed MGs (7.0/2.0 glands vs. 5.0/4.8 glands, P <0.01), and ocular staining (5.5/3.8 grade units vs. 0.5/1.0 grade units, P <0.01). The tests (area under curve, [AUC], odds ratio [OR]) that were most strongly associated with DE symptoms were ocular staining (0.93, 5.0), number of obstructed MGs (0.79, 2.6), meibum quality (0.76, 2.4), and NIBUT (0.74, 3.2) (all P <0.05). There was no significant difference between the two groups for the other DE tests (all P >0.05), and similarly, no significant association to DE symptoms (all P >0.05). Conclusion: The diagnostic tests most strongly associated with DE symptoms in older women were ocular staining, meibum quality, number of obstructed MGs, and tear film stability. Abstract : Supplemental Digital Content is Available in the Text.